Funcionalidade, sexualidade, autoimagem, autoestima, apoio social, solidão e espiritualidade de pessoas idosas institucionalizadas - Razeira, Tatiane Rocha (2021)
INTRODUCTION: The ageing process produces transformations, changes and adaptations in people's lives in different aspects: physiological, psychological, affective, sexual and sociocultural. OBJECTIVE: To verify the occurrence of an association between functionality, sexuality, self-image, self-esteem and loneliness, social support and spirituality in institutionalized elderly people. METHODS: Characterized as a cross-sectional and descriptive study, the study population was composed of 41 elderly people living in two philanthropic LTCFEs in the central region of the state of Rio Grande do Sul (RS). Sociodemographic factors and functionality, mobility, sexuality, self-esteem, self-image, social support, loneliness, and spirituality were investigated. RESULTS: Most participants in this study consider themselves sexually satisfied and are allowing themselves to experience their sexuality either with a partner or alone. About mobility, most participants were classified as independent in basic transfers and in functionality almost half of the participants were classified as independent for all activities. There was an association between loneliness and the affective factor of the social support scale, with the higher the loneliness score, the lower the affective support score. There was also an association between the scores of material support and loneliness, that is, elderly people who have more material support tend to have lower loneliness scores. With regard to loneliness and self-esteem, although not significant, a borderline positive association was observed between loneliness and self-esteem scores, elderly people with higher loneliness scores tend to have higher self-esteem scores. Although not significant, there was a borderline positive association between the scores of the emotional support factor and self-esteem, and elderly people with greater emotional support tend to have higher self-esteem scores. Regarding spirituality, the results show a good level of positivity and a low level of negativity. CONCLUSION: It is considered that the objective was reached, which allowed revealing facets and nuances specific to the investigated context, building knowledge about this population and about the researched topics. In general, elderly people participating in this study showed good levels in relation to the variables studied, which is very fruitful and nurturing.